2021
DOI: 10.1002/aic.17128
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory‐scale liquefiers for natural gas: A design and assessment study

Abstract: Exact knowledge of natural gas composition is essential in custody transfer to determine the energy content of the delivery. However, for liquefied natural gas (LNG), a reliable composition determination is difficult. Here, we describe the design of a laboratory‐scale reference liquefier that enables the validation and calibration of optical spectroscopy sensors by providing them with a sample of metrologically traceable composition. Hence, it is crucial to avoid fractionation of the sample during liquefaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…This only takes a few minutes. In a previous study, we observed that this variant is advantageous concerning changes in composition, compared to the variant described first [11]. It was shown that for the condensation into the precooled apparatus (green in Fig.…”
Section: Methodsmentioning
confidence: 83%
See 1 more Smart Citation
“…This only takes a few minutes. In a previous study, we observed that this variant is advantageous concerning changes in composition, compared to the variant described first [11]. It was shown that for the condensation into the precooled apparatus (green in Fig.…”
Section: Methodsmentioning
confidence: 83%
“…This would have a strong influence on the composition of the produced liquid sample in the measuring cell and must therefore be prevented (see section 3 and Ref. [11]). Although no vapor headspace is present in the measuring cell itself, the transition from liquid to vapor (and the liquid level) is located in the connecting tube between the measuring cell and the VLE-cell (see Fig.…”
Section: Methodsmentioning
confidence: 99%
“…As an outlook, future works may investigate whether the shift of the vacuum oscillation period will come to a standstill with a long-term study by constructive modifications at the densimeter unit or through an alternative operating protocol that avoids measurements of the vacuum oscillations period. Moreover, a worthwhile study would demonstrate whether a VTD-based apparatus can be used for density measurements on liquefied gas mixtures without changes in the composition of the liquefied sample [ 72 , 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…This may directly impact the uncertainty in measurement since a subtle change of the sample composition due to mistaken sample handling will distort the measurement result. Thus, maintaining the well-known sample composition within highly accurate synthetic experiments is crucial, which is, however, a challenging task (particularly for sample liquefaction) as shown in many of our experimental studies [67,[70][71][72][73][74][75]. It is striking that a large amount of experimental data is available for the methane + n-decane mixture.…”
Section: Statistical Evaluationmentioning
confidence: 95%